Choosing tomorrow's children the ethics of selective reproduction - Wilkinson, Stephen, 1965- (Oxford : Oxford University Press, 2010)
To what extent should parents be allowed to use reproductive technologies to determine the characteristics of their future children? Is there something morally wrong with choosing what their sex will be, or with trying to 'screen out' as much disease and disability as possible before birth? This book offers answers to such questions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human reproductive technology -- Moral and ethical aspects; Genetic engineering -- Moral and ethical aspects; Sex preselection -- Moral and ethical aspects